Disclosing new worlds entrepreneurship, democratic action and the cultivation of solidarity - Spinosa, Charles; Flores, Fernando; Dreyfus, Hubert L. 1929-2017 (MIT Press, 1997)
According to the authors, there are two major perils to history-making in Western society. One is the Cartesian tradition, which celebrates stepping back from everyday life to understand the world on the basis of rational deliberation. Against this, the authors advocate an intense involvement in the anomalies of everyday life as a means to understand the world and the changes it needs. The second is the neo-Nietzschean tendency to embrace radical, individual change for its own sake. Now that anyone can log on to the Internet to try on a new personality, the authors argue, it becomes increasingly urgent that we retrieve our history-making skills, both in our everyday lives and in our public roles
Keywords: Ondernemerschap; Politieke activiteit; Sociale verandering; Solidariteit; Sozialer Wandel; Social action; Collective behavior; Entrepreneurship; Social change; Innovation; Charisma; Führung; Kollektives Verhalten; Kreativität; Selbstverantwortung; Alltag; Sozialethik